Multiple Biomarkers of Anabolic Agent Administration in Urine as Candidates for Doping Diagnosis - PARK Jin Woo; Soo Hyun Lee; SON Junghyun (Proceedings of the 38th Cologne Workshop, 2020)
By certain drugs, biochemical change occurs and remains on our bodies. It is expected that if we discover metabolomic traces, we can apply it into doping diagnosis. We conducted a metabolomics research that a Liquid Chromatography-Quadrupole/Orbitrap Mass Spectrometer (Shimadzu LC ‒ Q-Exactive PlusTM, ThermoFisher Scientific) and Compound DiscovererTM 2.1 software (ThermoFisher Scientific) are involved. We prepared 15 urine samples of Adverse Analytical Finding (AAF) cases in anabolic agents, other 15 negative case samples, and a ‘pooled urine’ which all 30 urine samples were blended in each same volume. Deionized water, urine samples, and pooled urine were analyzed by Q-ExactiveTM in Full MS&ddMS2 mode, and then raw files were handled in Compound DiscovererTM for data analysis. As a result, 241 compounds of positive ions had p-values smaller than 0.05, meaning amount of those contents was significantly different between AAF cases and negative cases. Among negative ions, 559 compounds had p-values smaller than 0.05. Bilirubin concentration was elevated in AAF cases, and that implied one of adverse effects of anabolic agents is hepatotoxicity. Concentrations of conjugated metabolites of endogenous testosterone and dihydrotestosterone were lower in AAF cases, indicating as exogenous anabolic compounds were administered, the internal anabolic hormone was reduced by negative feedback for homeostasis. Obvious differences of metabolomic profiles between AAF and controls were observed and implied doping diagnosis via urine metabolomic profiles is possible.